1965
DOI: 10.2134/agronj1965.00021962005700040016x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Sulfur Deficiency of Alfalfa (Medicago sativa L.) from Plant Analysis1

Abstract: Synopsis Sulfur‐deficient alfalfa harvested at the early bloom stage contained less than 0.22% S and had a N:S ratio greater than 11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1969
1969
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…yields were not increased. Pumphrey and Moore (1965), Dijkshoorn and van Wijk (1967), and Stewart and Porter (1969) Maynard et al (1983), considered the plant Hl-reducible S:total S ratio to be more important than (N:S), in predicting seed yield of rape (8. n&pus and B. campestris)…”
Section: Resultsmentioning
confidence: 99%
“…yields were not increased. Pumphrey and Moore (1965), Dijkshoorn and van Wijk (1967), and Stewart and Porter (1969) Maynard et al (1983), considered the plant Hl-reducible S:total S ratio to be more important than (N:S), in predicting seed yield of rape (8. n&pus and B. campestris)…”
Section: Resultsmentioning
confidence: 99%
“…Sulphur concentration is one of the parameters commonly used to gauge the nutritional status of plants (Pumphrey and Moore, ; Schnug and Haneklaus, ) and to assess the nutritional value of forage plants for livestock (Qi et al ., ). Sulphur concentrations of forage plants are typically classified into four categories reflecting animal nutritional requirements: <1·0 g kg −1 , indicating deficient levels for all ruminants; >1·0 g kg −1 , indicating a satisfactory nutrition level for beef cattle; >1·6 g kg −1 , indicating a satisfactory nutritional level for adult sheep; and >2·0 g kg −1 , indicating a satisfactory nutritional level for dairy cows and ewes (NRC, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that increasing S supply increases shoot dry weight of alfalfa (Pumphrey and Moore, 1965;Seim et al, 1969). However, the effect of S supply on the relationship between alfalfa shoot and root production has received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…Drew and Suker, 1978;Hajabbasi and Schumacher, 1994;Mackie-Dawson, 1999). Pumphrey and Moore, 1965;Seim et al, 1969), but root morphological responses of alfalfa to S supply have attracted much less attention. Some reports have recognized the influence of S on the yield and quality of alfalfa (Medicago sativa L.) (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation